Płeć ludzka a tajemnica wcielenia Syna Bożego według św. Augustyna - Jaśkiewicz, Sylwester (Verbum Vitae, 2022)
The aim of the article is to present St. Augustine’s view of the male and female sexes (sexus) as reflected in his teaching on the Incarnation of the Son of God. The article focuses first on Augustine's commentary on the first chapters of Genesis: De Genesi ad litteram libri duodecim. This work is a precious testimony to the divine origin of human gender. The "man" (homo), in the Latin version of Genesis 1:26-27 available to Augustine, is both "man" (mas, masculus) and "woman" (femina, mulier). A woman differs from a man in both physiognomy and biological features, with still other differences belonging to the social realm, nevertheless, as to the dignity stemming from being made according to the image of God, women are equal to men. Just as in Christ the full dignity of the male sex is revealed, so in the Mother of Christ is the full dignity of the female sex made manifest. According to Augustine, Christ, although he could have created his own body from a rib (or from any member) of Mary – thus showing in his body that he was able to replicate what had occurred in the miracle of creation – he instead chose to show that in his mother's pure body, in the female sex itself, there is nothing embarrassing. Women will be resurrected in their female bodies, in which their essential beauty, bestowed at the time of creation, will be highlighted.